Frequency of Audit Committee Meetings and Firm Value: Environmental, Social, and Governance Disclosure (ESG) Roles - Fivi Anggraini; Silvira Helmi; Meihendri (Universitas Muhammadiyah Malang, 2025)
Purpose: This research aims to determine the mediating role of environmental, social, and governance (ESG) disclosures on the frequency of audit committee meetings and the value of energy companies in Indonesia from a scientific perspective. Methodology/approach: The data analysis method employed to test the hypotheses is structural equation modeling with partial least squares (SEM-PLS). The research sample comprises 80 companies in the energy sector listed on the Indonesia Stock Exchange during the period 2020–2022. Findings: This study successfully demonstrated that ESG disclosure acts as a mediator between the frequency of audit committee meetings and a company's value. Furthermore, the direct influence of audit committee meeting frequency and ESG disclosure significantly affects the company's value. Practical implications: The implications of this research can be that increasing the role of audit committees in overseeing and monitoring ESG issues is expected to have a positive impact on effective and strong ESG disclosures when the ideal frequency of audit committee meetings can be maintained. Originality/value: This research is providing evidence that the disclosure of ESG is one of the contributing factors in driving the increase in the value of companies in the energy sector in Indonesia, particularly with the presence of an adequate frequency of audit committee meetings.